Effect of parental touch on relieving acute procedural pain in neonates and parental anxiety (Petal): a multicentre, randomised controlled trial in the UK - Hauck, AGV; van der Vaart, M; Adams, E; Baxter, L; Bhatt, A; Crankshaw, D; Dhami, A; Evans Fry, R; Freire, MBO; Hartley, C; Mansfield, RC; Marchant, S; et al. (Elsevier, 2024)
Background Touch interventions such as massage and skin-to-skin contact relieve neonatal pain. The Parental touch trial (Petal) aimed to assess whether parental stroking of their baby before a clinically required heel lance, at a speed of approximately 3 cm/s to optimally activate C-tactile nerve fibres, provides effective pain relief.